Ecological Advancements and Developments of Agroforestry - Shitosri Mondal; Prodipto Bishnu Angon; Arpita Rani Roy (Turkish Journal of Agriculture: Food Science and Technology)
Agroforestry is a conventional method of land use that could help to address agricultural environmental issues. In order to take advantage of the ensuing ecological and economic interactions, agroforestry is the technique of consciously integrating woody vegetation (trees or shrubs) with crop and/or animal systems. According to recent studies, the global agri-food industry may reach more sustainable methods of producing food and fiber by adopting agroforestry techniques and principles more widely. This would benefit farmers economically and would benefit society as a whole in terms of the environment. Agroforestry promotes eco-intensification based on resource efficiency and offers a wide range of provisioning, regulating, cultural, supporting ecosystem services, and environmental advantages. In this review, we discussed agroforestry with its advantages and developments.